Efficiency of human monocyte-derived suppressor cell-based treatment in graft-versus-host disease prevention while preserving graft-versus-leukemia effect. (1st January 2021) - Janikashvili, Nona; Gérard, Claire; Thébault, Marine; Brazdova, Andrea; Boibessot, Clovis; Cladière, Claudie; Ciudad, Marion; Greigert, Hélène; Ouandji, Séthi; Ghesquière, Thibault; Samson, Maxime; Audia, Sylvain; et al.
ABSTRACT: Background: Immunosuppressive cell-based therapy is a recent strategy for controlling Graft- versus -Host Disease (GvHD). Such cells ought to maintain their suppressive function in inflammatory conditions and in the presence of immunosuppressive agents currently used in allogeneic hematopoietic cell transplantation (allo-HCT). Moreover, these therapies should not diminish the benefits of allo-HCT, the Graft- versus -Leukemia (GvL) effect. We have previously reported on a novel subset of human monocyte-derived suppressor cells (HuMoSC) as a prospective approach for controlling GvHD.Objective The objective of this study was to explore the therapeutic relevance of the HuMoSC in clinical conditions. Methods: Immune regulatory functions of HuMoSC were assessed in inflammatory conditions and in the presence of immunosuppressants. The therapeutic efficiency of the association of HuMoSC with immunosuppressants was evaluated in an experimental model of GvHD induced by human PBMC in NOD/SCID/IL2-Rγc −/− (NSG) mice. Interestingly, the inhibitory functions of HuMoSC against T lymphocytes and their ability to polarize Treg are preserved, in vitro, in inflammatory environments and are not affected by immunosuppressive agents. In vivo, the association of HuMoSC-based treatment with an immunosuppressive drug showed a synergistic effect for controlling GvHD. Furthermore, HuMoSC control GvHD while preserving GvL effect in a xeno-GvHD conditioned mouse model with cell neoplasm (CAL-1). HuMoSC are generated according to good manufacturing practices (GMP) and we demonstrated that these cells tolerate long-term preservation with unaltered phenotype and function.Conclusion HuMoSC-based therapy represents a promising approach for controlling GvHD and could be quickly implemented in clinical practice.